The Study Examines The Perceptions Of English Language Learners Participating In An International Internship Program In Satun, Thailand - Putri Marlida; Mandra Saragih (Journal on Education, 2024)
The purpose of this study is to determine how students see overseas internship programs from the standpoint of an entrepreneur. Qualitative descriptive methodologies are used in this investigation. For this investigation, five specifically chosen students were participated. These are EFL students who have worked in Thailand as foreign interns. Data gathering was completed by carrying out interviews. According to the study's findings, the majority of students thought the program was extremely helpful. Both of them intellectually as well as extracurricularly. From the standpoint of the entrepreneur, it was discovered that students who participated in the Participants in the program were given a wage, access to resources, and hands-on training that helped them become independent. Although there are a number of issues; this is only a technical area that needs improvement.